Penerapan Model Inkuiri Bebas dan Peta Konsep untuk Meningkatkan Pemahaman dan Kemampuan Mahasiswa dalam Memecahkan Masalah Lingkungan - Muhammad Taufik Awaludin (Pedagogia: Jurnal Ilmiah Pendidikan, 2016)
Higher education contributes to the improvement of students’ understanding and the change of behavior into being more responsible to the living environment. Strategies and approaches put as a learning model are required to solve the students’ problem related to environmental sensitivity. The models of free inquiry and concept mapping are able to plant the basics of scientific way of thinking in the students’ mind and help them develop critical thinking, creative and innovative patterns that can lead them to solve the problems related to the environment. The research is a classroom action research aimed at finding out a learning strategy which is more creative and innovative, improving students’ learning motivation, solving environmental problems and relating them to the students’ daily life. The research was conducted at Biology Education Study Program of Teacher Training and Educational Sciences Faculty, Pakuan University in the academic year of 2013-2014 involving the students of the third semester class A. The research consisted of two cycles. There were two treatments in each cycle. The research result shows that there was an improvement of students’ enthusiasm in the first cycle reaching 73% improved into 84% in the second cycle. The average score of students’ understanding on environmental pollution at the first cycle was 69.11% and the completion percentage was 66.67%, at the second cycle, the average score improved to 76.56 and the completion percentage became 83.33%. At the first cycle, the average score of students’ ability to solve environmental problems was 69.74 and the completion percentage was 63.33% at the second cycle, the average score improved to 77.69 and the completion percentage was 86.67%.